Implementation of Batho Pele Principles in the Greater Tzaneen Local Muncipality - Mboweni, Phanuel Cyril (University of Limpopo (Turfloop Campus), 2013)
The study deals with the implementation of the Batho Pele principles in the Greater Tzaneen Local Municipality. Literature review was conducted as a secondary source of information and primary information was collected from a sample of 23 respondents. The study used qualitative (semi-structured questionnaire, observation and document analysis) in data collection and analysis. The findings revealed that the root causes of the challenges and the challenges themselves that the Greater Tzaneen Local Municipality is facing, are mainly internal and include the following: Low morale, budget constraints, lack of enforcement of the Batho Pele principles by both employees and their supervisors, poor employee attitudes, unwillingness to improve towards service delivery, lack of monthly and quarterly meetings where review of all programmes and projects is done. Instead review is done at the end of the year, shortage of human resource in the Community Services Directorate to effectively and efficiently implement systems, lack of sufficient performance incentives to reward those who perform well or exceed the set performance target or halo effect, focusing on the quantity of the end-product (output) rather than on the quality.
Thesis (MPA) --University of Limpopo, 2013
Keywords: Service delivery; Municipality; 352.439; Public administration; Municipal services